Optically excited spin pumping mediating collective magnetization dynamicsin a spin valve structure - Danilov, A.P.; Scherbakov, A.V.; Glavin, B.A.; Linnik, T.L.; Kalashnikova, A.M.; Shelukhin, L.A.; Pattnaik, D.P.; Rushforth, A.W.; Love, C.J.; Cavill, S.A.; Yakovlev, D.R.; Bayer, M. (American Physical Society, 2018)
We demonstrate spin pumping, i.e. the generation of a pure spin current by precessing magnetization, without application of microwave radiation commonly used in spin pumping experiments. We use femtosecond laser pulses to simultaneously launch the magnetization precession in each of two ferromagnetic layers of a Galfenol-based spin valve and monitor the temporal evolution of the magnetizations. The spin currents generated by the precession cause a dynamic coupling of the two layers. This coupling has dissipative character and is especially efficient when the precession frequencies in the two layers are in resonance, where coupled modes with strongly different decay rates are formed.